In vivo optical modulation of neural signals using monolithically integrated two-dimensional neural probe arrays - Son, Yoojin; Lee, Hyunjoo Jenny; Kim, Jeongyeon; Shin, Hyogeun; Choi, Nakwon; Lee, C. Justin; Yoon, Eui-Sung; Yoon, Euisik; Wise, Kensall D.; Kim, Tae Geun; Cho, Il-Joo (NATURE PUBLISHING GROUP, 2015)
Integration of stimulation modalities (e.g. electrical, optical, and chemical) on a large array of neural probes can enable an investigation of important underlying mechanisms of brain disorders that is not possible through neural recordings alone. Furthermore, it is important to achieve this integration of multiple functionalities in a compact structure to utilize a large number of the mouse models. Here we present a successful optical modulation of in vivo neural signals of a transgenic mouse through our compact 2D MEMS neural array (optrodes). Using a novel fabrication method that embeds a lower cladding layer in a silicon substrate, we achieved a thin silicon 2D optrode array that is capable of delivering light to multiple sites using SU-8 as a waveguide core. Without additional modification to the microelectrodes, the measured impedance of the multiple microelectrodes was below 1 MO at 1 kHz. In addition, with a low background noise level (+/- 25 mu V), neural spikes from different individual neurons were recorded on each microelectrode. Lastly, we successfully used our optrodes to modulate the neural activity of a transgenic mouse through optical stimulation. These results demonstrate the functionality of the 2D optrode array and its potential as a next-generation tool for optogenetic applications.
Keywords: WAVE-GUIDES; LIGHT DELIVERY; BRAIN; AMYGDALA; ASTROCYTES; CHANNELS; RELEASE; NEURONS; MEMORY; GABA